1D Genome Sequencing on the Oxford Nanopore MinION. (11th July 2017) - Goodwin, Sara; Wappel, Robert; McCombie, W. Richard
Abstract: Today's short‐read sequencing instruments can generate read lengths between 50 bp and 700 bp depending on the specific instrument. These high‐throughput sequencing approaches have revolutionized genomic science, allowing hundreds of thousands of full genomes to be sequenced, and have become indispensable tools for many researchers. With greater insight has come the revelation that many genomes are much more complicated than originally thought and include many rearrangements and copy‐number variations. Unfortunately, short‐read sequencing technologies are not well suited for identifying many of these types of events. Long‐read sequencing technologies can read contiguous fragments of DNA in excess of 10 kb and are much better suited for detecting large structural events. The newest long‐read sequencing instrument is the MinION device from Oxford Nanopore. The rapid sequencing speed and low upfront instrument cost are features drawing interest in this device from the genomics community. This unit provides a representative protocol for carrying out human genome sequencing on the Oxford Nanopore MinION. © 2017 by John Wiley & Sons, Inc.